Direitos indígenas entre fronteiras: cidadania, presença e mobilidade ticunas na tríplice fronteira do Brasil, Colômbia e Peru - Medeiros, Augusto Karol Marinho (2013)
This thesis aims to analyze the problems of mobility Ticunas Indians in the triple border of Brazil, Colombia and Peru, which follows cultural issues and social rights guaranteed in different form, in the legal system of the countries they inhabit. To better understand this problem be related to the Ticunas right to live in their territories according to their lifestyles, and social question put to state law - not only in Brazil, but also Colombian and Peruvian - mobility and traffic across borders, intensified contemporaneously on the Brazilian side, according to the benefits and social services offered by the Brazilian State, and not in the same way by neighboring states. The Brazilian State in this region is then watching a great demand on these benefits by Ticunas, including coming across the border to apply for social rights guaranteed only to Indian citizens. We will discuss the consolidation of national borders and therefore the process of nationalization that affected the way of life and territorial dynamics of indigenous border. We will do a comparative study on the Constitution of Brazil, Colombia and Peru in relation to indigenous rights offered by the social policies of nation states. Finally evidenciaremos posture of the Brazilian state before the increased demand for social services demanded by foreign Ticunas and appropriate action to address the problem as cooperation agreements between the countries located in the upper Amazon. Keywords: Ticunas. Mobility. Indigenous law. National borders.